PENYULUHAN TENTANG PENGETAHUAN REMAJA AWAL TENTANG PENCEGAHAN HIV DI SMP N 1 BLAMBANGAN - Febriyanti, Hellen (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2024)
HIV transmission in adolescents is influenced by peers, misunderstandings about sex, the influence of mass media and increased internet access that makes adolescents vulnerable to arousing pornography so that they have unsafe sex and are vulnerable to HIV. The purpose of carrying out this Community Service is to increase adolescent knowledge about HIV and HIV prevention, so that adolescents can get information about HIV. The stages of Community Service include the Initial stage, the implementation stage and the final stage. Community Service activities can increase early adolescent knowledge about HIV and HIV prevention.